Application of gradient dose segmented analysis as a treatment quality indicator for patients undergoing volumetric modulated arc radiotherapy - Van Reenen, Christoffel Jacobus (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.